Complete Genome Sequence Analysis of the First Imported Mpox Virus Clade Ib Variant in China - Yin Song; Yong Yan; Jingyu Xu; Shencong Lv; Ganglin Ren; Yamei Zhou; Wanchen Song; Rui Ge; Peihua Xu; Guoying Zhu; Zhongwen Chen (Pathogens)
Mpox, a zoonotic disease caused by the mpox virus (MPXV), has seen a significant shift in its epidemiological status since 2022, evolving from an initial local outbreak to a global epidemic. This recent outbreak of MPXV mainly emerged in several European and American countries and subsequently spread to over 100 countries and regions worldwide. The rapid evolution of MPXV, coupled with increased international interactions, has led to a gradual rise in mpox cases in certain regions of Asia, mostly involving MPXV clade II and its branch strains. In contrast, the more pathogenic and clinically severe MPXV clade Ib has been relatively rare, with no reports in China to date. Here, we analyzed the whole gene sequence of imported MPXV clade Ib variant from the first infection case detected in China. Through whole genome sequencing, we successfully obtained a full-length MPXV genome of 195,405 base pairs (bp). Phylogenetic analysis revealed that the genetic sequence of the MPXV in this case was predominantly clustered with MPXV clade Ib sequences previously reported from multiple African and European countries. Compared with the MPXV clade Ib reference strain DQ011155.1, there are 127 nucleotide alterations and 57 amino acid mutations in the MPXV genome of this case. Given that the MPXV clade Ib has started to appear in China, we must pay more attention to the prevention of and control measures for the spread of mpox.